Analisis Faktor yang Berpengaruh Terhadap Kualitas Laba - Fitriya Mufidah; Subadriyah Subadriyah (AKUNTANSI 45, 2024)
This study aims to analyze the factors that affect the quality of the company's profits. The methods used in this study are descriptive analysis and multiple linear regression. The data used is in the form of secondary data obtained from the financial statements of companies listed on the Indonesia Stock Exchange. The results of the study show that several factors such as leverage, company size, and sales growth have a significant influence on the quality of profits. In addition, this study also found that profit management through accrual affects the quality of reported profits. These findings provide important insights for stakeholders in understanding the factors that affect profit quality and their implications for financial decision-making.